Evaluasi Kinerja Sistem Angkutan Umum Terintegrasi Daerah Masamba - Lili, Ahmad; Said, Lambang Basri; Maryam, St (INTEK: Jurnal Penelitian, 2019)
This study aims to analyze the evaluation of theperformance of transportation mode services and theperformance of transport route services to evaluate theperformance of the service level of integrated public transportsystems in the Masamba Region. The method of data collection isconducted through primary surveys and secondary surveys.Primary surveys are carried out by distributing questionnairesand data analysis techniques using SmartPLS version 3.0software and secondary surveys by collecting data related toresearch themes in several related agencies. The research sampleis that the public transportation passengers on the Masamba-Makassar Bus route as many as 98 respondents, determining thenumber of samples can be done using the Bernoulli formula.Based on the analysis of existing data obtained by respondents'perceptions that the performance of the level of service of thetransportation mode in terms of safety, comfort and orderlinesshas been effective, although in terms of equality it still needs toimprove its services. The performance of the Bus publictransport system in the Masamba area has also created anintegrated public transport system and the performance of theMasamba-Makassar PO route services is categorized well basedon the standards of public transport services from the DirectorGeneral of Land Transportation.